Low energy impact on the interface of bamboo-steel composites. Issue 12 (15th October 2019) - Zhang, Zhen-wen; Li, Yu-shun; Liu, Rui; Zhang, Jia-liang
ABSTRACT: The bamboo-steel composite structure is a newly developed structure, combining Phyllostachys Pubescens (also called Moso bamboo) plywood and cold-formed thin-walled steel with structural adhesive. The aim of this study is to investigate the debonding propagation mechanism in detail at the bamboo-steel adhesive bonding interface (bamboo-steel interface) under low-energy impact using a progressive failure model. A three-dimensional cohesive zone model with reloading traction-separation law was adapted to simulate and characterize the progressive adhesive debonding at the bamboo-steel interface. Results show that the model can predict the failure behavior of the bamboo-steel interface under low-energy impact. The stress distribution and debonding propagation of the bamboo-steel interface were analyzed. The results reveal that the debonding is mostly due to the shear stress and the tensile peeling stress at the impact loading stage and the unloading stage, respectively. Furthermore, analyses of the impact failure show that the shear stress at the impact loading stage is generated by the tangential sliding between the steel sheet and bamboo plywood due to different flexural stiffness, while the tensile peeling stress at the unloading stage is due to the normal separation owing to different rebounding of the two different materials.